Respons Fisiologis Ayam KUB (Kampung Unggul Balitbangtan) dan Ayam Walik dengan Haplotipe Gen HSP70 Berbeda yang Terpapar Cekaman Panas Akut - Any Aryani; Dedy Duryadi Solihin; Cece Sumantri; Rudi Afnan; Tike Sartika (Jurnal Ilmu Pertanian Indonesia, 2021)
This study was conducted to determine the physiological response of acute heat stress in Kampung Unggul Balitbangtan (KUB) and Walik chickens with four different HSP70 gene haplotypes (H1', H1, H2, and H3). Acute heat stress is carried out at 35°C for one hour. The data was analyzed based on rectal temperature measurements, distribution of body surface temperature (head, neck, body, and leg area), hormone levels (corticosterone and triiodothyronine), and time of panting. Body surface temperature is detected using infrared thermography. The results showed that haplotype H1 Walik chicken is more susceptible to heat stress based on the rectal temperature. In contrast, H1' haplotype Walik chicken released more heat through the body surface in the leg area. Keywords: heat stress, hormone, KUB chicken, infrared thermography, walik chicken